Bridging Gut Inflammation and Cognitive Decline: Exploring the Pathogenesis of Inflammatory Bowel Disease-associated Dementia - Dr. Yati Sharma (Asian Journal of Pharmaceutics (AJP), 2025)
Dementia, characterized by a progressive decline in cognitive functions such as memory, thinking, problem-solving, language, and behavior, is most commonly associated with Alzheimer’s disease, a prevalent neurodegenerative disorder. Recent epidemiological evidence suggests a potential link between inflammatory bowel disease (IBD) and dementia, prompting investigations into this association. This abstract reviews current research on the pathogenesis of IBD-associated dementia, focusing on animal model studies that mimic chronic intestinal inflammation similar to IBD. The pathogenesis of IBD is related to dysbiosis of the gut microenvironment, and various epidemiological studies show that patients with IBD are more likely to have dementia in future. Thus, targeting IBD as a potential therapeutic approach for dementia has garnered increasing attention. Furthermore, IBD-induced neuroinflammation affects brain function and contributes to dementia. In this review, we highlight the role of microbiota and their metabolites in mediating the pathogenesis of IBD-associated dementia. Disruptions in gut microbiota can lead to altered metabolite profiles that may influence neuroinflammatory pathways and exacerbate cognitive impairment. Furthermore, immune-mediated mechanisms play a critical role in this process. The microbiota-gut-brain axis, which links gut microbiota with brain function, has emerged as a significant pathway through which IBD-related changes in microbiota and metabolites contribute to dementia. Overall, the research underlines the complex interplay between chronic intestinal inflammation, microbiota alterations, and immune responses in the development of dementia associated with IBD.